Impact of acute covid-19 on cardiac function in the long term: a systematic review (Revista Contexto & Saúde, 2025)
The present study aimed to evaluate the relationship between elevated biomarkers due to COVID-19 infection and possible permanent damage to the heart muscle. This is a systematic review including studies with eligible randomized clinical trials and case-control studies. Papers’ eligibility criteria were adults diagnosed and treated for COVID-19 and assessment of cardiac biomarkers during the acute phase of COVID-19 infection, with symptoms or not, without previous structural or functional changes related to the cardiovascular system and who, after a minimum of after 30 days, cardiac structural assessment was obtained through imaging tests, either echocardiogram or cardiac magnetic resonance. The findings were not robust when analyzing the association between the elevation of secondary cardiac biomarkers to COVID-19 and the presence of late cardiac sequelae. Based on the cost-effectiveness ratio for adopting such strategy, it becomes unjustifiable to perform it routinely in the Brazilian Unified Health System. It is more appropriate and less costly to adopt health promotion strategies, individualized attention, multidisciplinary therapeutic approach, frequent clinical surveillance and specialized assessment when affected by COVID- 19, reducing damage caused to the cardiocirculatory system, minimizing spending on public health exams and better effectiveness in collective health with care practices.
Keywords: Biomarkers; Troponin; Brain Natriuretic Peptide; Myocardium; COVID-19